81‐1: High Transmittance and High Contrast LCD for 3D Head‐Up Displays. Issue 1 (30th May 2018) - Murata, Mitsuhiro; Yokoyama, Ryoichi; Tanaka, Yoshiki; Hosokawa, Toshihiko; Ogura, Kenji; Yanagihara, Yasuhiro; Kusafuka, Kaoru; Matsumoto, Takuya
Abstract : We achieved high transmittance and high contrast with keeping high response speed by using high aperture ratio technology and high efficiency liquid crystal. Transmittance is improved by 149% from initial mass production by using this technology, We are available this new liquid crystal technology for 3D‐HUD with parallax barrier.